Construction of Bismuth Oxyhallide-based Heterojunction-structured Composite and Its Environmental Application for Water Treatment - (:unkn) unknown (My University, 2019)
With the rapid development of the global economy, environmental protection and sustainable development have become the main trends of current society. In particular, water pollution and energy shortage are outstanding issues that need to be solved in a clean and sustainable way. Recently, semiconductor-based photocatalytic technology, an environmentally friendly technique, has attracted enormous attention and become an emerging research hotspot in the application of water/wastewater treatment and generation of renewable energy as it can convert infinite solar energy into chemical energy. Conventional semiconductor materials usually have a relatively large band gap that only responds to the ultraviolet light, which largely limits their practical applications. Therefore, design of novel efficient photocatalytic materials that can be excited by visible light or solar light is a promising research direction. Bismuth oxyhalides have been drawing increasing interest as promising photocatalysts for their suitable band gaps, low cost, nontoxicity and chemical stability. Besides, formation of heterojunction structure by coupling two or more semiconductors is usually considered as an effective approach to further improve the photocatalytic activities of catalysts. Hence, in this study, BiOBr/Bi12O17Cl2 heterojunction-structured materials were synthesized by a facile in situ chemical deposition-precipitation method and a series of characterization methods were employed to analyze the as-prepared samples. The photocatalytic properties were investigated by degrading several typical model organic contaminants under the irradiation of simulated solar light or visible light. The BiOBr/Bi12O17Cl2 composite exhibited superior photocatalytic performance over pure BiOBr and Bi12O17Cl2. Additionally, the mass ratio between BiOBr and Bi12O17Cl2 was optimized to get the heterojunction composite with highest photocatalytic activity. What’s more, the plausible reason for such enhancement of photocatalytic reaction and a possible photocatalytic mechanism interpreted through the quenching effect of different scavengers were discussed. The present work could provide a facile strategy to synthesize novel highly efficient and stable bismuth-based photocatalysts at room temperature for environmental applications.
Keywords: Bismuth Oxyhalides; Heterojunction Composite; Photocatalysis; Water Treatment